Cohesive Devices Found on Emma Watson’s Speech Entitled ‘Gender Equality’ - Abidah, Nasikhatul; Laili, Elisa Nurul (International Journal of English and Applied Linguistics (IJEAL), 2024)
This research focuses on the types of cohesive devices which are used in speech. Cohesion is the relationship between one element and another in a written or spoken text. It is used to express ideas through grammar and vocabulary. This speech was held on Saturday, September 20 2014, at a special event for the HeForShe campaign. This study is considered descriptive qualitative. The research instrument is the writer because the writer is the one who is able and understands to analyse and obtain the data. The steps to collect the data are reading and understanding all the data many times. The next step is categorizing texts to be analyzed easier. The last step is describing the findings and concluding them. The findings of this study show that both cohesion types are found in the data. The types of grammatical cohesion found in the data are reference, substitution, and conjunction.  Both of lexical cohesion are found in the data, those are reiteration and collocation. It shows that the speaker uses grammatical and lexical methods.